2019
DOI: 10.1101/636449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Glycolytic Protein Phosphofructokinase Dynamically Relocalizes into Subcellular Compartments with Liquid-like Properties in vivo

Abstract: While much is known about the biochemical regulation of glycolytic enzymes, less is understood about how they are organized inside cells. Here we built a hybrid microfluidic-hydrogel device for use in Caenorhabditis elegans to systematically examine and quantify the dynamic subcellular localization of the rate-limiting enzyme of glycolysis, phosphofructokinase-1/PFK-1.1. We determine that endogenous PFK-1.1 localizes to distinct, tissue-specific subcellular compartments in vivo. In neurons, PFK-1.1 is diffusel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 105 publications
(172 reference statements)
0
7
0
Order By: Relevance
“…The absence of phosphofructokinase, like the absence of other glycolytic proteins, results in impaired synaptic vesicle endocytosis during transient hypoxia (Jang et al, 2016). Through the use of a microfluidic device that allows precise control of transient cycles of normoxia and hypoxia, we can tempo-rally control the endocytic reaction (Jang et al, 2021). We examined ATG-9 localization in the synaptic Zone 3 region (Figures 2B and 2B 00 ).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of phosphofructokinase, like the absence of other glycolytic proteins, results in impaired synaptic vesicle endocytosis during transient hypoxia (Jang et al, 2016). Through the use of a microfluidic device that allows precise control of transient cycles of normoxia and hypoxia, we can tempo-rally control the endocytic reaction (Jang et al, 2021). We examined ATG-9 localization in the synaptic Zone 3 region (Figures 2B and 2B 00 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, enzymes are known to be concentrated at specific subcellular compartments to perform spatially defined cellular functions. Via liquid-liquid phase separation, enzymes such as GIT1 and b-Pix can autonomously form highly concentrated molecular assemblies, providing a novel mechanism for enriching limited amounts of enzymes into specific cellular regions for fast and spatially defined catalysis (Jang et al, 2019;Webb et al, 2017). Guided by the atomic structures of GIT1, b-Pix, and the GIT/b-Pix complex, we also demonstrated that phase separation-mediated GIT1/b-Pix complex condensation, instead of the classical binary interaction between GIT1 and b-Pix, is required for the enzyme complex to modulate cell migration and synapse formation.…”
Section: Llmentioning
confidence: 99%
“…The absence of phosphofructokinase, like the absence of other glycolytic proteins, results in impaired synaptic vesicle endocytosis during transient hypoxia (Jang et al, 2016). Through the use of a microfluidic device that allows precise control of transient cycles of normoxia and hypoxia, we can temporally control the endocytic reaction (Jang et al, 2020). We examined ATG-9 localization in the synaptic Zone 3 region (Figure L-L'), in which we can observe discrete and interspersed presynaptic specializations (compare to the Zone 2 region ( Figure 2B-B'), which consists of one large and continuous presynaptic area).…”
Section: Atg-9 Undergoes Exo-endocytosis At Presynaptic Sitesmentioning
confidence: 99%
“…To inhibit oxidative phosphorylation by hypoxia, a reusable microfluidic polydimethylsiloxane (PDMS) microfluidic device was used, as described (Jang et al, 2020) while imaging ATG-9::GFP localization in pfk-1.1(gk922689);olaIs34…”
Section: Inhibiting Oxidative Phosphorylation Using a Microfluidic-hymentioning
confidence: 99%